2004
DOI: 10.1586/14737175.4.2.219
|View full text |Cite
|
Sign up to set email alerts
|

Road to recovery: drugs used in stroke rehabilitation

Abstract: The practice of neurorehabilitation is unique in that it supplements treatments with medications which complement and expedite the rehabilitation process. In stroke rehabilitation, medications can be used not only to treat poststroke secondary complications but also to facilitate recovery. Since only thrombolytics have been demonstrated to be effective in minimizing brain damage and maximizing functional outcome, intensive rehabilitation remains the most significant and important means by which stroke survivor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Verbal memory encoding was improved by ACE-inhibitors in individuals with multiple sclerosis (Krupp et al, 2004). For stroke, a case study reported dramatic improvements in sensorimotor function of hemiplegic lower limb and shoulder as a result of treatment with the ACE-inhibitor donezepil (Zorowitz, 2004). A subsequent trial that tested constrained-induced motor therapy with combined donepezil application, versus placebo application, demonstrated higher gains on the Wolf Motor Function Test in the donepezil group approaching statistical significance (Nadeau et al, 2004).…”
Section: Pharmacological Approaches Proposed To Facilitate Training Ementioning
confidence: 99%
“…Verbal memory encoding was improved by ACE-inhibitors in individuals with multiple sclerosis (Krupp et al, 2004). For stroke, a case study reported dramatic improvements in sensorimotor function of hemiplegic lower limb and shoulder as a result of treatment with the ACE-inhibitor donezepil (Zorowitz, 2004). A subsequent trial that tested constrained-induced motor therapy with combined donepezil application, versus placebo application, demonstrated higher gains on the Wolf Motor Function Test in the donepezil group approaching statistical significance (Nadeau et al, 2004).…”
Section: Pharmacological Approaches Proposed To Facilitate Training Ementioning
confidence: 99%
“…113 AchET inhibitors have shown to improve verbal memory encoding in individuals with multiple sclerosis. 114 A few studies of participants with stroke have reported improvements in sensorimotor function of the hemiplegic limb 115-116 and improved speech 117 when motor training was combined with AchET inhibitors such as donepezil. Although cholinergic agents are generally safe, they have potentially troubling side effects such as nausea, diarrhea, and weight loss, which do not make them a popular choice.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on animals revealed that using amphetamine increases dopamine and noradrenaline release and also inhibits re-uptake of neurotransmitter by presynaptic neuron, which may have a therapeutic effect after brain injury [42]. Motor training can be reinforced by the administration of amphetamines, which potentially decrease motor impairment, as was demonstrated in several clinical trials [43]. Drugs increasing activity of the cholinergic system (i.e.…”
Section: Neuroplasticity and Brain Repair After Strokementioning
confidence: 99%
“…Donepezil, Galantamine, Rivastigmine, Tacrine), which is responsible for modulating neuronal activity in the cerebral cortex, are also considered helpful in improving the effects of post-stroke rehabilitation [43]. Moreover, the pharmacotherapy used for improving memory and executive functions in Alzheimer disease is also associated with the improvement of sensorimotor functions in patients following stroke [43]. Studies on treatments with selective serotonin reuptake inhibitor (SSRIs) suggest also that SSRIs may enhance recovery after stroke [44].…”
Section: Neuroplasticity and Brain Repair After Strokementioning
confidence: 99%